Infective endocarditis in developing countries: An update - Mutagaywa, Reuben K.; Vroon, Josephine C.; Fundikira, Lulu; Wind, Anna Maria; Kunambi, Peter; Manyahi, Joel; Kamuhabwa, Apollinary; Kwesigabo, Gideon; Chamuleau, Steven A. J.; Cramer, Maarten J.; Chillo, Pilly (Frontiers in Cardiovascular Medicine, 2022)
Introduction Despite advances in diagnostic and treatment, morbidity and mortality due to infective endocarditis (IE) has not decreased. There is a discrepancy in epidemiology of IE between developed and developing countries. Over the last years, increased awareness and consequently prevalence of rheumatic heart disease (RHD) and congenital heart disease (CHD) which are considered predisposing conditions for IE, is noted. Here, we present a review of literature on IE in developing countries. Methods We conducted a non-systematic literature search through PubMed and Embase. We have divided the studies into two groups: studies published before 2015 (group 1) and studies  2015 (group 2). The outcome was defined as a difference in epidemiology, microbiology, treatment, and mortality over time. The Scale for Assessment of Narrative Review Articles guidelines was applied. Findings In total, 16 studies were included. The total number of IE cases was 1,098 and 1,505 in groups 1 and 2 respectively. We compared 4/7 cohorts from group 1 (n = 789) with 5/9 cohorts from group 2 (n = 636). Males predominated in all studies. RHD was higher in group 1 than in group 2 (42.3% vs 30.3%, p<0.001) while for CHD there was no change (17.6% vs 16.7%, p = 0.672). Streptococci infections was lower in group 1 than group 2 (26.2% vs 37.7%, p<0.001). The proportion of Staphylococcus aureus was 15.3% in group 1 and 23.6% in group 2, p<0.001. Negative blood culture (NBC) was higher in group 1 than in group 2 (42.2% vs 34.1%, p=0.002). Patients in group 1 received more surgery than in group 2 (38.8% vs 28.8%, p<0.001). Mortality was similar in the two groups (20.9% vs 22.3%, p = 0.518). Conclusion This review highlights that IE is prevalent in developing countries. RHD and CHD are common predisposing conditions. Prosthetic, degenerative valve disease, intravenous drug use, and HIV are also risk factors. While the presence of streptococci and staphylococcus has increased, the number of NBC and patients getting surgery has decreased. Mortality has not changed over time. Timely diagnosis and management of patients with RHD and CHD and comprehensive management of IE are warranted